2021
DOI: 10.5435/jaaos-d-20-00357
|View full text |Cite
|
Sign up to set email alerts
|

Robotics and Navigation as Learning Tools for Fellows Training in Hip Arthroplasty

Abstract: Introduction: The association between implant malpositioning and complications has been repeatedly demonstrated. Recently, technological advancements have allowed for more consistent implant placement. Beyond this obvious application, these technologies may also serve as a learning tool. Thus, the aim of this study was to evaluate the accuracy of fellows' estimation of implant positioning using a robotic system. Methods: Data were prospectively collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A study reported that in the absence of a robotic system, cups were placed beyond the bounds of the safe zone as defined by Lewinnek and Callanan in approximately 43.47% and 69.57% of patients, respectively 25 . An effective way to improve the implant placement accuracy during THA is to tailor the implants to the patient's anatomy 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study reported that in the absence of a robotic system, cups were placed beyond the bounds of the safe zone as defined by Lewinnek and Callanan in approximately 43.47% and 69.57% of patients, respectively 25 . An effective way to improve the implant placement accuracy during THA is to tailor the implants to the patient's anatomy 30 .…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the robot-assisted implantation of the acetabular cup could get more accurate anteversion, a more reasonable LLD, and a higher proportion of the prosthesis position in the Lewinnek's safe zone. Robot-assisted THA surgery has been a reliable surgical technique in recent years 13,[24][25][26][27] . Ilmen et al reported that robotic-assisted THA improved acetabular component accuracy compared with conventional THA.…”
Section: Precise Cup Positioningmentioning
confidence: 99%
“…18 They reported a notable difference between estimated and actual cup version but no notable differences between estimated and actual cup inclination or femoral broach position. 18 In another recent study, Deckey et al 19 suggested that robotic technology can potentially be useful as a learning tool for residents by allowing for visual preoperative case planning and providing intraoperative feedback to trainees through real-time evaluation of soft-tissue balancing in TKAs. The authors noted, however, that training in robotics should not compromise the acquisition of surgical skills needed for manual procedures.…”
Section: Discussionmentioning
confidence: 94%
“…18,19 A recent study compared intraoperative orthopaedic fellow estimations of acetabular reamer and femoral broach placement with real-time actual positioning as measured by a robotic system. 18 They reported a notable difference between estimated and actual cup version but no notable differences between estimated and actual cup inclination or femoral broach position. 18 In another recent study, Deckey et al 19 suggested that robotic technology can potentially be useful as a learning tool for residents by allowing for visual preoperative case planning and providing intraoperative feedback to trainees through real-time evaluation of soft-tissue balancing in TKAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation